The Analysis of Factors Affecting Exclusive Breastfeeding in Grobogan Regency - Novitasari, Tri (Public Health Perspective Journal, 2019)
Exclusive breastfeeding is the giving of breast milk (ASI) in newborns to 6 monthsÃ‚Â  babies without being given drinks or other food, breast milk can be given up to 2 years. Coverage of Exclusive ASI in Central Java Province 2017 (54.5%). In Grobogan Regency 2015 (67.67%), 2016 (10.18%), 2017 (11.1%), 2018 (10.38%). The research objective was to analyze the factors that influence exclusive breastfeeding in Grobogan Regency. The research was using cross sectional design. The research sample was 92 respondents that were obtained by cluster random sampling technique. Data collection techniques were interviews, observation, questionnaire. Data analysis in the study used the Chi Square test and logistic regression test. The results found no influence of family support variables (p = 0,000), prenatal guidance (p = 0,000), the role of midwives (0,000), culture (0,000), no effect of venostyle style (p = 0.493) on exclusive breastfeeding in Grobogan Regency. The most influential variables were prenatal guidance with p = 0,000; EXP (B) / OR = 0.040. Health centers in Grobogan Regency need to improve cadre orderliness, increase counseling for mothers and the community.Ã‚Â